2020
DOI: 10.14233/ajchem.2021.22982
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization of Ceftibuten-Copper(II) Complex and Prediction of Its Biological Activity

Abstract: Ceftibuten dihydrate, one of the third-generation cephalosporin antibiotic is effectively used in curing several infectious diseases. The complexation of drug with metal may enhance the antibacterial activity. In this work, a new complex of ceftibuten dihydrate with Cu(II) was synthesized, characterized and antibacterial activity is reported. The in vitro test showed that the antibacterial activity of complex of ceftibuten was greatly enhanced against Staphylococcus aureus and Salmonella typhi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Analyzing IR data of ceftibuten dihydrate (Figure 3a), it was found that lactam (C=O) and carboxyl (C=O) bands appear at 1770 and 1651 cm -1 , respectively. Like Cu(II)complex 24 of ceftibuten dihydrate, significant changes in the frequency of lactam (C=O) was not observed in Ni(II)-complex of pure drug as well. It means that the carbonyl group of lactam ring was not involved in the formation of coordination complexes of ceftibuten dihydrate.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Analyzing IR data of ceftibuten dihydrate (Figure 3a), it was found that lactam (C=O) and carboxyl (C=O) bands appear at 1770 and 1651 cm -1 , respectively. Like Cu(II)complex 24 of ceftibuten dihydrate, significant changes in the frequency of lactam (C=O) was not observed in Ni(II)-complex of pure drug as well. It means that the carbonyl group of lactam ring was not involved in the formation of coordination complexes of ceftibuten dihydrate.…”
Section: Resultsmentioning
confidence: 91%
“…29,36 The frequency of 3 o N atom present in β-lactam ring of parent drug is shifted (1361→ 1103 cm -1 ) in the complex, due to involvement of 3 o N atom in chelation. 24,34,35 There was a new peak found at 478 cm -1 in the FT-IR spectrum of the complex [Figure 3(b)] which was due to  (Ni-N). 32 El Tabl et al reported a peak at 480 cm -1 for Ni-N bond in Ni(II)complexes of L-amino acids, used as foliar fertilizers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations